2011
DOI: 10.1088/1742-5468/2011/11/p11018
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of metrics in complex networks with applications in functional brain networks

Abstract: Abstract. An increasing number of network metrics have been applied in network analysis. If metric relations were known better, we could more effectively characterize networks by a small set of metrics to discover the association between network properties/metrics and network functioning. In this paper, we investigate the linear correlation coefficients between widely studied network metrics in three network models (Bárabasi-Albert graphs, Erdös-Rényi random graphs and Watts-Strogatz small-world graphs) as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 54 publications
(113 reference statements)
3
60
0
Order By: Relevance
“…The measure M A,B (k) is different from the scalar correlation of topological metrics [39]. When we compare all the nodes (k = 100%), we have a full overlap and M A,B (100%) = 1.…”
Section: Definition 51 For Two Node Rankingsmentioning
confidence: 99%
“…The measure M A,B (k) is different from the scalar correlation of topological metrics [39]. When we compare all the nodes (k = 100%), we have a full overlap and M A,B (100%) = 1.…”
Section: Definition 51 For Two Node Rankingsmentioning
confidence: 99%
“…It is very likely however, that these measures are highly correlated and can be replaced by a smaller number of more independent measures. A simulation study showed that most graph measures can be clustered into 2 to 4 groups, depending upon the topology of the underlying network (Li et al, 2011). For example, in the case of Erdős Rényi random graphs a strong correlation between the clustering coefficient and the average shortest path length can be expected.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Similarly, every vertex in a tree graph has a depth. Selecting and studying graph properties of networks is a challenging problem as illustrated by Li et al [2011]. This chapter focuses on trees with specific graph properties that influence the performance of several distributed applications.…”
Section: Graph Properties and Applicationsmentioning
confidence: 99%